Small Missional Church as an alternative in the period of Church Decline in Korea - Tan, An-wei (Ecclesial Futures, 2023)
This article examines the causes and circumstances of the decline of Korean churches since the 2000s. After briefly sketching the history and critical events of the growth of the Korean church, it pays attention to one of the leading reasons people leave the church and a reason that the Korean church has lost its reliability in the view of much of Korean society. After that, the author introduces two phenomena in the process of the slow growth and decline of the Korean church: the phenomenon of “believing without belonging” and the increase in numbers of bi-vocational ministers. This is a time when the missional church has begun to emerge as a new type of church, different from the traditional church, and at the same time non-institutional churches have emerged as a missional approach to believing without belonging. Furthermore, the author argues that the small missional church is a helpful alternative and required paradigm in the context of the decline of the Korean church by using several case studies, including shared worship space, bi-vocational ministry, and local missional church.